Face image resolution and perceived attractiveness: An 8K display study - Koji Mizukoshi; Yoshihiro Hamanaka; Xiaoguang Yang; Takaya Oishi; Hideaki Kawabata (PLoS ONE, 2026)
Background Facial attractiveness is shaped by multiple visual cues, yet the influence of image resolution on attractiveness judgments remains underexplored. Advances in display and imaging technology now allow for image presentation at resolutions approaching the limits of human spatial vision, enabling investigations under higher-fidelity spatial sampling conditions that more closely approximate retina-like detail at typical viewing distances. Objectives This study aimed to determine whether facial image resolution, specifically matched to the spatial resolving power of the human visual system, affects perceived facial attractiveness. Methods High-resolution facial images of 180 Japanese female models were captured using an 8K imaging system (7680 × 4320 pixels; 283.2 ppi). Low-resolution versions (35.3 ppi) were created by downsampling the originals using pixelation. Both high- and low-resolution images were presented on an 8K display in a within-subjects design. Participants rated the attractiveness of each face using a standardized 6-point scale. Results Facial images presented at higher resolution received slightly higher attractiveness ratings than their low-resolution counterparts, as confirmed by linear mixed-effects models accounting for crossed observer and identity effects. The effect was especially pronounced for faces with higher baseline attractiveness. Age-related declines in attractiveness ratings were observed in both conditions. Conclusions Ultra-high image resolution yields a small but reliable increase in perceived facial attractiveness, particularly for faces with higher baseline attractiveness. These findings suggest that increased spatial detail may amplify attractiveness-related cues that are otherwise diminished in conventional-resolution displays.